Excess Intermolecular Free Length and Molecular Interaction for Some Binary Liquid Mixtures - Sharma, Dhirendra; Srivastava, S.N. (Asian Journal of Chemistry, 2010)
The concept of intermolecular free length has been applied to some binary liquid mixtures namely 1-chloro naphthalene + decane, 1-chloro naphthalene + dodecane, benzene + pxylene and benzene + p-dioxane. The intermolecular interaction study was made through the excess free length for the systems under investigation. The free length (Lf) values obtained by the two methods have been compared. The results are consistent with the theories.